Sistem Informasi Seleksi Beasiswa Menggunakan Metode SAW (Studi Kasus: Prodi Geofisika FMIPA UNIB) - Sihotang, Hizkia Tigor; Oktoeberza , Widhia KZ (Universitas Bengkulu, 2023)
Geophysics is one of the study programs in the Faculty of Mathematics and Natural Sciences at Bengkulu University. Students in this program are eligible for regular scholarships, which are scholarships specifically designated for students in the Faculty of Mathematics and Natural Sciences who lack funding for their studies. There are two important aspects related to this information system. First, the admission process is still done manually, where students have to bring their documents and requirements to the program in order to apply for the scholarship. In this research, the researchers used a system development method to facilitate interaction between developers and users during the application development process. The application was created using PHP language with the Codeigniter framework, designing the process model using DFD model, and MySQL as the database. The resulting system is called the